2016
DOI: 10.1016/j.ophtha.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes with Anti–Vascular Endothelial Growth Factor Treatment of Neovascular Age-Related Macular Degeneration

Abstract: Purpose To describe outcomes 5 years after initiation of treatment with bevacizumab or ranibizumab for neovascular age-related macular degeneration (AMD). Design Cohort study.. Participants Patients enrolled in the Comparison of AMD Treatments Trials (CATT). Methods Patients were randomly assigned to ranibizumab or bevacizumab and to 1 of 3 dosing regimens. After 2 years, patients were released from the clinical trial protocol. At approximately 5 years, patients were recalled for examination. Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
363
10
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 565 publications
(402 citation statements)
references
References 40 publications
(48 reference statements)
21
363
10
8
Order By: Relevance
“…At the 2-year endpoint of the CATT trial, subjects in all 4 of the anti-VEGF treatment arms showed large mean improvements in visual acuity from baseline. During the next 3 years, patients received fewer mean number of injections as part of standard care and for the population as a whole, all of the visual gains achieved during the first 2 years were lost (45). While there are a number of possible causes for this loss of vision, it appears that insufficient treatment may have contributed because (a) the goal of treatment is to eliminate fluid within or under the macula, but fluid was present in 83% of 555 eyes in which spectral domain OCT was obtained, a very large percentage; (b) intraretinal fluid is particularly problematic because it is a risk factor for poor outcome and more eyes had intraretinal fluid at 5 years than at 2 years (61% versus 50%); and (c) VEGF suppression prevents growth of choroidal NV, but in 467 eyes in which fluorescein angiography was done at 5 years, total lesion area was 4.8 mm 2 larger than at 2 years, an increase of more than 50%, indicating that there had been poor VEGF suppression.…”
Section: Discussionmentioning
confidence: 99%
“…At the 2-year endpoint of the CATT trial, subjects in all 4 of the anti-VEGF treatment arms showed large mean improvements in visual acuity from baseline. During the next 3 years, patients received fewer mean number of injections as part of standard care and for the population as a whole, all of the visual gains achieved during the first 2 years were lost (45). While there are a number of possible causes for this loss of vision, it appears that insufficient treatment may have contributed because (a) the goal of treatment is to eliminate fluid within or under the macula, but fluid was present in 83% of 555 eyes in which spectral domain OCT was obtained, a very large percentage; (b) intraretinal fluid is particularly problematic because it is a risk factor for poor outcome and more eyes had intraretinal fluid at 5 years than at 2 years (61% versus 50%); and (c) VEGF suppression prevents growth of choroidal NV, but in 467 eyes in which fluorescein angiography was done at 5 years, total lesion area was 4.8 mm 2 larger than at 2 years, an increase of more than 50%, indicating that there had been poor VEGF suppression.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] However, the striking visual acuity gains seen after two years of treatment in a clinical trial were completely lost three years after patients exited the trial and initiated standard care methodologies. 10 Many of the patients who lost initial visual acuity gains had subretinal hyper-reflective material suggestive of subretinal fibrosis or areas of macular atrophy. Subretinal hyper-reflective material is a risk factor for macular atrophy, so one possible hypothesis is that over time many patients develop subretinal fibrosis despite treatment with anti-VEGF agents because other HIF-1-stimulated vasoactive agent stimulates subretinal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…There is no effective treatment for most cases of AMD; however, a small proportion of patients with well-defined CNV benefit from laser photocoagulation [24] . Recent advances in the development of intravitreal antiangiogenic therapies (anti-VEGF antibody injection) for neovascular AMD have greatly improved clinical outcomes in the last decade; however, vision improvement during the first 2 years was not maintained at 5 years, and monthly treatments were associated with an increased risk of developing geographic atrophy [27] . Currently, treatments remain inadequate for atrophic AMD [26] .…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%